Determining the appropriate pretreatment procedures and the utility of liver tissue for bulk stable isotope ( δ 13 C and δ 15 N ) studies in sharks - K. Blue Pahl; David J. Yurkowski; Sabine P. Wintner; Geremy Cliff; Matthew L. Dicken; Nigel E. Hussey (Journal of Fish Biology, 2021)
Stable‐isotope analysis (SIA) provides a valuable tool to address complex questions pertaining to elasmobranch ecology. Liver, a metabolically active, high turnover tissue (~166 days for 95% turnover), has the potential to reveal novel insights into recent feeding/movement behaviours of this diverse group. To date, limited work has used this tissue, but ecological application of SIA in liver requires consideration of tissue preparation techniques given the potential for high concentrations of urea and lipid that could bias δ 13 C and δ 15 N values ( i.e ., result in artificially lower δ 13 C and δ 15 N values). Here we investigated the effectiveness of (a) deionized water washing (WW) for urea removal from liver tissue and (b) chloroform‐methanol for extraction of lipids from this lipid rich tissue. We then (a) established C:N thresholds for deriving ecologically relevant liver isotopic values given complications of removing all lipid and (b) undertook a preliminary comparison of δ 13 C values between tissue pairs (muscle and liver) to test if observed isotopic differences correlated with known movement behaviour. Tests were conducted on four large shark species: the dusky (DUS, Carcharhinus obscurus ), sand tiger (RAG, Carcharias taurus ), scalloped hammerhead (SCA, Sphyrna lewini ) and white shark (GRE, Carcharodon carcharias ). There was no significant difference in δ 15 N values between lipid‐extracted (LE) liver and lipid‐extracted/water washed (WW) treatments, however, WW resulted in significant increases in %N, δ 13 C and %C. Following lipid extraction (repeated three times), some samples were still biased by lipids. Our species‐specific “C:N thresholds” provide a method to derive ecologically viable isotope data given the complexities of this lipid rich tissue (C:N thresholds of 4.0, 3.6, 4.7 and 3.9 for DUS, RAG, SCA and GRE liver LEWW tissue, respectively). The preliminary comparison of C:N threshold corrected liver and muscle δ 13 C values corresponded with movement/habitat behaviours for each shark; minor differences in δ 13 C values were observed for known regional movements of DUS and RAG (δ 13 C Diffs = 0.24 ± 0.99‰ and 0.57 ± 0.38‰, respectively), while SCA and GRE showed greater differences (1.24 ± 0.63‰ and 1.08 ± 0.71‰, respectively) correlated to large‐scale movements between temperate/tropical and pelagic/coastal environments. These data provide an approach for the successful application of liver δ 13 C and δ 15 N values to examine elasmobranch ecology.